Combining CD38 antibody with CD47 blockade is a promising strategy for treating hematologic malignancies expressing CD38 - Li, Song; Chen, Dianze; Yang, Yanan; Guo, Huiqin; Liu, Dandan; Sun, Nana; Bai, Xing; Wang, Kaili; Li, Tengfei; Li, Guanghui; Yang, Chunmei; Zhang, Wei; et al. (Frontiers in Immunology, 2024)
Background: CD38 and CD47 are expressed in many hematologic malignancies, including multiple myeloma (MM), B-cell non-Hodgkin lymphoma (NHL), B-cell acute lymphoblastic leukemia (ALL), and B-cell chronic lymphocytic leukemia (CLL). Here, we evaluated the antitumor activities of CD38/CD47 bispecific antibodies (BsAbs). Methods: Five suitable anti-CD38 antibodies for co-targeting CD47 and CD38 BsAb were developed using a 2+2 “mAb-trap” platform. The activity characteristics of the CD38/CD47 BsAbs were evaluated using in vitro and in vivo systems. Results: Using hybridoma screening technology, we obtained nine suitable anti-CD38 antibodies. All anti-CD38 antibodies bind to CD38+ tumor cells and kill tumor cells via antibody-dependent cellular cytotoxicity (ADCC) and antibody-dependent cellular phagocytosis (ADCP). Five anti-CD38 antibodies (4A8, 12C10, 26B4, 35G5, and 65A7) were selected for designing CD38/CD47 BsAbs (IMM5605) using a “mAb-trap” platform. BsAbs had higher affinity and binding activity to the CD38 target than those to the CD47 target, decreasing the potential on-target potential and off-tumor effects. The CD38/CD47 BsAbs did not bind to RBCs and did not induce RBC agglutination; thus, BsAbs had much lower blood toxicity. The CD38/CD47 BsAbs had a greater ability to block the CD47/SIRPα signal in CD38+/CD47+ tumor cells than IMM01 (SIRPα Fc fusion protein). Through Fc domain engineering, CD38/CD47 BsAbs were shown to kill tumors more effectively by inducing ADCC and ADCP. IMM5605-26B4 had the strongest inhibitory effect on cellular CD38 enzymatic activity. IMM5605-12C10 had the strongest ability to directly induce the apoptosis of tumor cells. The anti-CD38 antibody 26B4 combined with the SIRPα Fc fusion proteins showed strong antitumor effects, which were better than any of the mono-therapeutic agents used alone in the NCI-H929 cell xenograft model. The CD38/CD47 BsAbs exhibited strong antitumor effects; specifically, IMM5605-12C10 efficiently eradicated all established tumors in all mice. Conclusion: A panel of BsAbs targeting CD38 and CD47 developed based on the “mAb-tarp” platform showed potent tumor-killing ability in vitro and in vivo. As BsAbs had lower affinity for binding to CD47, higher affinity for binding to CD38, no affinity for binding to RBCs, and did not induce RBC agglutination, we concluded that CD38/CD47 BsAbs are safe and have a satisfactory tolerability profile.